Förbättrad fosforrening i LD-konverter genom tillsatser av kalksten - Söderström, Daniel (2016)
The steel industry is continuously facing higher demands on its products. This together with the increasing amount of lower quality raw material is a growing challenge for the industry. Steel manufacturers, such as SSAB in Luleå are continuously working to adapt to the higher demands and more challenging premises. This is done by continuously working to improve their processes in order to use the new and more difficult material to handle. This master thesis aims to improve the phosphorous refining capacity of the LD- converters at the SSAB steel plant in Luleå by adding limestone to the converters instead of lime as a slag former at the early stages of converting.In this work a number of reference charges were examined by extracting steel and slag samples from the process. This was done in order to set a frame of reference to be used further into the work. Tests were conducted by adding limestone together with the scrap before adding the hot metal to the furnace. Also some charges were interrupted at 30 % through the process in order to extract slag and iron samples.The main part of the results was analyzed using multivariate techniques such as PCA and PLS. Two PCA models were created for the reference and test charges respectively. The full dataset was examined using PLS and later parted into a model which only consisted of charges with a certain scrap quality.The charges that were interrupted at 30 % through the process were analyzed by a statistical hypothesis test, in which it was concluded that no effect could be seen on the phosphorous related variables concerning mean values between references and tests.The multivariable analysis concluded in models showing both increased and decreased phosphorous capacity of the converters when using limestone as slag former. Overall the models showed improvement in the phosphorous capacity apart from the endpoint phosphorous in the steel, which was positive in one model and negative in the other model. It was concluded that there exists effects of using limestone on the ...